Individual variation and vulnerability to angling: No apparent behavioral differences among fish captured using different fishing gears. (15th October 2021) - Pollack, Lea; Wiltsee, Laura; Beittel, Alice; Ganzorig, Batsaikhan; Jensen, Olaf P.
Abstract: It is well known that fishing is size‐selective, but harvest may also inadvertently target certain behavioral types or personalities. Changes in the abundance of behavioral types within a population have implications for fisheries management, including affecting catch rates, individual growth, and food web dynamics. Using streamside behavioral assays, we quantified the repeatability of behaviors in a population of Baikal grayling ( Thymallus baicalensis ) in northern Mongolia, a popular sport fish and important local predator. We assessed whether different angling techniques (i.e., fly or spinning gear) collected different behavioral types and whether variation in behavior was associated with body condition or diet (i.e., using stable isotope analysis). Surprisingly, we found no evidence for consistent individual differences in several behaviors within this population. Furthermore, differences in mean behaviors were not predicted by angling gear, body condition, or carbon and nitrogen isotopic signatures. We suggest that since this is a fished population, the range of behavioral variability in the population may have been reduced through previous behaviorally selective harvest. This might explain both the lack of difference in mean behaviors between fish caught by both gear types and the lack of evidence for consistent individual differences in behavior within the sampled population.